A LETTER FROM SPECIAL EDITION EDITOR IN CHIEF - DR. VASANTHAN. R - R, Vasanthan. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Department of English (UAP) has successfully organised a Two-Day International Conference on "Learning Language and Literature for Life (4L)" on the 9th and 10th of September 2022. About 44 colleges participated in the conference, and a total of 270 presenters attended it. Parallel sessions were conducted at four venues with the distinguished keynote speakers, Dr. P.K Patra from Bodoland University, Assam; Dr. Seng Tong Chong, University Tenaga Nasional, Malaysia; Dr. Mohammed Shamsul Hoque, Daffodil International University, Bangladesh; Dr. Pasa Tevfik Cephe, Gazi University, Turkey and Dr. Michael Greaney, Lancaster University, United Kingdom. The presentation sessions were chaired by prominent resource persons from various colleges in Tamil Nadu. The conference's main objective was to encourage scholars to have an insight into the different areas of English language and literature research. The discussions during the paper presentations proved to be a great opportunity for exchanging knowledge among great minds. Among the 270 papers received, 17 papers related to scope were selected to be published in the UGC Care-Listed Journal "ShodhKosh: Journal of Visual and Performing Arts" as a special issue titled "Depiction of Women in Artistic Works". I express my sincere thanks to the publisher of Granthaalayah Publications for his noble partnership with the institution to motivate researchers with due recognition. The Department of English (UAP) looks forward to take this partnership to the next level with substantial research contributions to promote art forms in general and literary arts in particular. Sincerely, Dr. Vasanthan.R